HIV/AIDS : Update Terkini di Indonesia - Natasya Natasya; Shella Nur Maharani; Misna Misna (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
HIV/AIDS poses a considerable public health challenge on a global scale, and Indonesia is no exception. The HIV virus can be transmitted through several pathways, including mother-to-child transmission during pregnancy, childbirth, and breastfeeding, as well as through unprotected sexual intercourse and the use of non-sterile medical equipment. Studies have shown that delivering a baby via caesarean section can lower the risk of HIV transmission compared to vaginal delivery. Additionally, breastfeeding from HIV-positive mothers may heighten the chances of passing the virus to their infants, particularly under certain conditions. To reduce the risk of HIV transmission, preventive measures such as antiretroviral therapy (ARV) are vital, especially for serodiscordant couples—those in which one partner is HIV-positive while the other is not. Furthermore, social support and counseling play critical roles in encouraging adherence to treatment regimens among patients. This research aims to deepen our understanding of HIV transmission and to investigate effective preventive strategies that can significantly lower the risk of infection.